PDE6D Inhibitors with a New Design Principle Selectively Block K-Ras Activity - Farid A. Siddiqui; Catharina Alam; Petja Rosenqvist; Mikko Ora; Ahmed Sabt; Ganesh babu Manoharan; Lakshman Bindu; Sunday Okutachi; Marie Catillon; Troy Taylor; Omaima M. Abdelhafez; Harri Lönnberg; et al. (AMER CHEMICAL SOC, 2022)
The trafficking chaperone PDE6D (also referred to as PDE delta) has been nominated as a surrogate target for K-Ras4B (hereafter K-Ras). Arl2-assisted unloading of K-Ras from PDE6D in the perinuclear area is significant for correct K-Ras localization and therefore activity. However, the unloading mechanism also leads to the undesired ejection of PDE6D inhibitors. To counteract ejection, others have recently optimized inhibitors for picomolar affinities; however, cell penetration generally seems to remain an issue. To increase resilience against ejection, we engineered a "chemical spring" into prenyl-binding pocket inhibitors of PDE6D. Furthermore, cell penetration was improved by attaching a cell-penetration group, allowing us to arrive at micromolar in cellulo potencies in the first generation. Our model compounds, Deltaflexin-1 and -2, selectively disrupt K-Ras, but not H-Ras membrane organization. This selectivity profile is reflected in the antiproliferative activity on colorectal and breast cancer cells, as well as the ability to block sternness traits of lung and breast cancer cells. While our current model compounds still have a low in vitro potency, we expect that our modular and simple inhibitor redesign could significantly advance the development of pharmacologically more potent compounds against PDE6D and related targets, such as UNC119 in the future.